A novel missense mutation in the UBE2A gene causes intellectual disability in the large X‐linked family. (7th January 2021) - Arslan Satılmış, Saide Betül; Kurt, Emin Emre; Akçay, Ebru Perim; Sazci, Ali; Ceylan, Ahmet Cevdet
Abstract: Background: X‐linked intellectual disability type Nascimento (XIDTN) is a disorder of the ubiquitin‐proteasome pathway of protein degradation controlled by the UBE2A gene. The disease is characterized by intellectual disability, speech impairment, dysmorphic facial features, skin and nail anomalies, and, frequently, seizures. Eight affected males from a four‐generation family who have intellectual disability and speech disorders were examined within an extended family of 57 individuals. Methods A number of methods were used for the molecular diagnosis. Conventional karyotype analyses, array‐based comparative genomic hybridization (aCGH), whole exome swquencing (WES), sanger sequencing were performed. Results First, the conventional karyotype analyses were normal, and the results of the aCGH analyses were normal. Then, WES revealed a novel missense mutation of the UBE2A gene at exon 4 NM_003336.3: c.182A>G (p.Glu61Gly). Seven affected individuals and nine carriers in the multigenerational, large family were diagnosed through Sanger sequencing. Conclusions: We identified the mutation causing intellectual disability in the large family and demonstrated its phenotypic effects. Our cases showed that dysmorphic features could be considered mild, whereas intellectual disability and speech disorders are common features in XIDTN. The structure and function of the gene will be better understood in the novel UBE2A mutation. The genotype–phenotype correlation and phenotypic variations in XIDTN were identified through a literature review. Accordingly, XIDTN should be considered in individuals who exhibit an X‐linked pedigree pattern and have intellectual disability and speech disorders. Abstract : Eight affected males who have intellectual disability and speech disorder in four‐generations family were examined to identify the etiology. Whole‐exome sequencing revealed a novel missense mutation of the UBE2A gene at exon 4 NM_003336.3:c.182A>G (p.Glu61Gly), which causes X‐linked intellectual disability type Nascimento (XIDTN). The genotype–phenotype correlation and phenotypic variations in XIDTN were identified through a literature review.